The Existence of Presidential Authority in Determining a State of Emergency - Komendangi, Rivanka Amelia Nursyahbani (CV. Rayyan Dwi Bharata, 2024)
The declaration of a state of emergency by a President is an important instrument in maintaining state stability and security in crisis and emergency situations. The President's authority in handling emergencies raises many debates about the limits of his power in taking extraordinaire actions to protect national interests. The purpose of this study is to analyze and understand the existence of the President's authority in determining a state of emergency. This research uses normative juridical research methods by collecting data from various sources such as the constitution, laws and regulations, court decisions, and related literature. The results of this study show that the President's authority in determining a state of emergency is related to three main aspects, namely the initial decision, the implementation of emergency measures, and restrictions on constitutional rights. The President has the authority to determine a state of emergency based on serious threats to national security or territorial integrity.